Characterisation of the first electronically excited state of protonated acetylene C2H3+ by coincident imaging photoelectron spectroscopy. (17th January 2021) - Garcia, Gustavo A.; Loison, Jean-Christophe; Holzmeier, Fabian; Gans, Bérenger; Alcaraz, Christian; Nahon, Laurent; Wu, Xiangkun; Zhou, Xiaoguo; Bodi, Andras; Hemberger, Patrick
ABSTRACT: We present a combined experimental and theoretical study of the threshold photoelectron spectroscopy of the vinyl radical encompassing the first triplet excited state of the vinyl cation. The radicals were produced in a flow-tube reactor by hydrogen abstraction of C2 H4 and CH4 using fluorine atoms generated in a microwave discharge. Vinyl was ionised with synchrotron vacuum ultraviolet radiation. A double imaging coincidence setup was used to record the threshold photoelectron spectrum. The experimental and simulated spectra show a marked adiabatic transition to the a ~ + 3 A′′ state with a short vibrational progression dominated by the C = C stretching mode. The adiabatic ionisation energy to this state is measured precisely at 10.747 ± 0.008 eV. In combination with the adiabatic ionisation energy to the X ~ + 1 A1 state from the Active Thermochemical Tables (ATcT), we find a singlet–triplet gap of 2.27 ± 0.01 eV (219 ± 1 kJ mol −1 ). Calculated ionisation energies and Franck–Condon factors for the singlet A ~ + 1 A′′ excited state are also given. GRAPHICAL ABSTRACT: